2010
DOI: 10.2337/dc09-1630
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Cream, Glucose, and Orange Juice on Inflammation, Endotoxin, and the Expression of Toll-Like Receptor-4 and Suppressor of Cytokine Signaling-3

Abstract: OBJECTIVEWe have recently shown that a high-fat high-carbohydrate (HFHC) meal induces an increase in plasma concentrations of endotoxin (lipopolysaccharide [LPS]) and the expression of Toll-like receptor-4 (TLR-4) and suppresser of cytokine signaling-3 (SOCS3) in mononuclear cells (MNCs) in addition to oxidative stress and cellular inflammation. Saturated fat and carbohydrates, components of the HFHC meal, known to induce oxidative stress and inflammation, also induce an increase in LPS, TLR-4, and SOCS3.RESEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
188
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(199 citation statements)
references
References 26 publications
7
188
0
4
Order By: Relevance
“…This study also found upregulation of Ifit3, Clec4a3, Slc22a3, and C3ar1, genes regulated by LPS-stimulated macrophages. These data are in line with the reported increase in LPS concentrations upon high-fat ingestion (28,46) resulting from lipid-induced disruption of the intestinal barrier (28). Interestingly, LPS is also known to decrease TWEAK signaling (47).…”
Section: Figure 2 Time Courses Of Circulating Metabolites and Hormonsupporting
confidence: 80%
“…This study also found upregulation of Ifit3, Clec4a3, Slc22a3, and C3ar1, genes regulated by LPS-stimulated macrophages. These data are in line with the reported increase in LPS concentrations upon high-fat ingestion (28,46) resulting from lipid-induced disruption of the intestinal barrier (28). Interestingly, LPS is also known to decrease TWEAK signaling (47).…”
Section: Figure 2 Time Courses Of Circulating Metabolites and Hormonsupporting
confidence: 80%
“…However, recently, it has been shown that moderate postprandial glucose excursions are not able to increase TLR expressions and that the major mediators of TLR activation may be free fatty acids and specific macronutrients such as saturated fat (17,34,35). It is also relevant that insulin exerts an opposite, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, plasma sICAM-1 did not change and CRP rose only marginally. In another study, a meal rich in cream increased the expression of IL-1b and TNF-a in mononuclear cells (Depurkar et al, 2010). Van Wijk et al (2006) tested 50 g fat cream meals in diabetic patients with Table 4 Plasma concentrations of the eight inflammatory and atherogenesis-related biomarkers following 4 weeks on each of two test diets (fermented dairy and unfermented dairy) and the mixed dairy fat run-in and washout periods no effect on either CRP or MCP-1 levels but a delayed rise in IL-6 at 4 h. High-fat meals based on peanut butter, cream, eggs and cheese lowered TNF-a after 4 h but raised IL-6 while CRP concentration was unchanged (Blackburn et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The fat-rich test meals have generally included several sources of fat including meat fat, eggs and dairy fats (Esposito et al, 2003;Blackburn et al, 2006;van Wijk et al, 2006;Manning et al, 2008;Depurkar et al, 2010;El-Khoury et al, 2010). Individual dairy fats have not been specifically tested, which may be important given the findings in a large prospective study, suggesting a cardioprotective effect from consuming fermented but not non-fermented dairy foods (Warrensjo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%